Pengaruh Struktur Modal Terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2013 - Haninun HANINUN; Feby Angelina (Universitas Bandar Lampung (UBL), 2016)
In order to meet the needs of the funds used to operate and develop the business, the company must be able to obtain or provide the required capital in a way that is effective and efficient, whether the capital come from internal or external. It is a matter of financial structure and capital structure which is used to measure the profitability of a company. The purpose of this study is to determine empirically the effect of capital structure variables that proxy with Debt Equity Ratio and Times Interest Earned on profitability variable proxied by Return On Equity. The data used in this study were obtained from the annual financial statements of each manufacturing company published through the official website www.idx.co.id. Samples are taken as many as 41 companies listed in Indonesia Stock Exchange during the period from 2011 to 2013 were taken through purposive sampling method. Data analysis techniques in this study using multiple regression analysis. The results showed that in partial Debt Equity Ratio with regression value of 0.048 and a significant positive effect on the variable Return On Equity, while variable for 0,010 Times Interest Earned positive but not significant effect on the variable Return On Equity. This suggests that the use of debt and capital as well as the ability of the company to pay a fixed load of interest being the size of the company to obtain additional funds so as to improve profitability.